A new key for the species of Ateuchus Weber (Coleoptera: Scarabaeidae: Scarabaeinae) occurring in Mexico, with a description of the first North American inquiline species from a rodent burrow (Rodentia: Geomydae) and new distribution records - Kohlmann,Bert (2018)
Abstract The first Ateuchus Weber (Scarabaeinae) species, A. tuza sp. nov., from a rodent burrow from North America is described. Diagnostic characters are presented; photographs of an adult male and illustrations of male genitalia are included. A key for all known Mexican Ateuchus Weber species is provided. Ateuchus hornai (Balthasar) is revalidated. New distribution records from Mexico and Central America are reported.